A USER-FRIENDLY COMPUTER CODE FOR RADIATED EMISSION AND SUSCEPTIBILITY ANALYSIS OF PRINTED CIRCUIT BOARDS - Carlsson, Jan (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A user-friendly computer code, PCB-MoM, that is intended to be used in EMC applications for predicting radiated emission and susceptibility of printed circuit boards (PCB) is presented. The formulation is based on an electric field integral equation (EFIE) expressed in the frequency domain. The EFIE is solved by the method of moments using two-dimensional pulse bsis functions and one-dimensional pulse test functions. In order to incorporate dielectric material in the substrate a spectral domain formulation is used. The code has been validated by comparison with previously published results and results obtained by other methods and codes.